A Modified Game Approach to Improving the Learning Outcomes of Students in Physical Education Volleyball Instruction - Putra, Muklas Safi'i; Abadi, Muhammad Nur; Khatami, Muhammad Reza; Emily, Nadya; Antika, Nartik (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2025)
This study aims to improve students' learning outcomes on the underhand serve technique in volleyball through a modified game approach in physical education (PE) classes at SMP Negeri 47 Surabaya. The main issue addressed is the low motivation and skill level of students in performing the underhand serve, caused by the lack of variation in teaching methods and the use of inappropriate equipment. This classroom action research (CAR) was conducted in two cycles involving 30 eighth-grade students from class VIII A. The modification applied involved using plastic balls instead of standard volleyballs to make it easier for students to master the underhand serve technique. Data were collected through tests, observation, and documentation, and analyzed using descriptive quantitative methods. The results showed a significant improvement in students’ learning outcomes, with mastery learning increasing from 73.31% in cycle I to 93.34% in cycle II. The use of modified games proved effective in increasing students' motivation, participation, and skills in learning the underhand serve in volleyball. Therefore, the modified game approach can serve as an innovative solution to improve learning outcomes in PE, particularly in volleyball material